Cloning of the encoding phospholipase c3 gene from two mungbean (Vigna radiata (L.) Wilczek) cultivars kp11 and mn93 - Thanh Thanh, Nguyen Vu; Mau, Chu Hoang; Van, Pham Thi; Binh, Le Tran (Academia Journal of Biology, 2014)
Mungbean Vigna radiata (L.) Wilczek is a grain legume widely grown in the tropics and subtropics and is an excellent source of dietary protein. Many biotic and abiotic stresses such as disease and drought limit the mungbean yield. In this study, 2 mungbean cultivars KP11 and MN93 were subjected to PCR analysis using 3 primer pairs (F1, F2, F3). A 4.2 k b phospholipase C3 (PLC3) gene fragment from the mungbean genome was successfully amplified by PCR. The PCR products containing the PLC3 fragments were cloned in pTZ57R/T and sequenced with three primer pairs (3 forward and 3 reverse primer). The cloned PLC3 gene had 4215 nucleotides in length, including start codon and stop codons, intron and exon. The coding region of PLC3 comprised 1776 nucleotides, encoding a polypeptide of 591 amino acids.